The Green Economy Concept as Development Strategy of Cempaka Tourism Village toward Sustainable Tourism Development - Mohamad Heri Hidayattuloh; Azis Nur Bambang; Amirudin Amirudin (The Indonesian Journal of Planning and Development, 2020)
Green economy is an economic concept that aims to improve human welfare, reduce inequality, and preserve the environment and carry out development that is in line with the carrying capacity of the environment. Tegal Regency has a complete tourist attraction consisting of natural attractions and special interest attractions. One of the special interest attractions being developed is Cempaka Tourism Village, Bumijawa District. This Cempaka Tourism Village relies on the concept of populist economy based on local wisdom and the beauty of the natural environment. The purpose of this study is to inventory the potential and attractiveness of Cempaka Tourism Village and to prioritize the most suitable tourism potential in the development of Cempaka Tourism Village as a means of improving the community's economy based on the concept of a green economy. This paper employs both the qualitative and quantitative methods. The analytical tool used is the Analytical Hierarchy Process (AHP) method with the help of the Expert Choice application. Based on the results, it can be seen that Cempaka Tourism Village has the potential and attractiveness to be developed into a tourist village with the concept of a green economy. The best priority in the development of Cempaka Tourism Village is to utilize the Slumpring Market as an alternative to improve the environment-based community economy.